Some fractional integral inequalities of Hermite Hadamard and Minkowski type - Hernádez Hernández, Jorge Eliecer (2019)
This article presents some fractional integral inequalities of the Hermite-Hadamard and Minkowski type using the fractional integral operator defined by R.K. Raina (2016) in [1], which generalize some previous results found by L. Bougoffa [5] and S.S. Dragomir [7].